Safe and Sound Banking : A Role for Countercyclical Regulatory Requirements? - Caprio, Gerard, Jr. (World Bank, Washington, DC, 2014)
Most explanations of the crisis of 2007-2009 emphasize the role of the preceding boom in real estate and asset markets in a variety of advanced countries. As a result, an idea that is gaining support among various groups is how to make Basel II or any regulatory regime less pro-cyclical. This paper addresses the rationale for and likely contribution of such policies. Making provisioning (or capital) requirements countercyclical is one way potentially to address pro-cyclicality, and accordingly it looks at the efforts of the authorities in Spain and Colombia, two countries in which countercyclical provisioning has been tried, to see what the track record has been. As explained there, these experiments have been at best too recent and limited to put much weight on them, but they are much less favorable for supporting this practice than is commonly admitted. The paper then addresses concerns and implementation issues with countercyclical capital or provisioning requirements, including why their impact might be expected to be limited, and concludes with recommendations for developing country officials who want to learn how to make their financial systems less exposed to crises.